PENILAIAN RISIKO BENCANA TANAH LONGSOR DESA WANADRI KECAMATAN BAWANG KABUPATEN BANJARNEGARA - Khasyir, Muhamad; Aji, Ananto; Setyaningsih, Wahyu (Geo-Image, 2016)
The research aims to find out threats, vulnerability,and capacity of landslide disaster, also analyse the risk level of landslide at Wanadri Village. The research method is disaster risk assesment method. Disaster risk assesment is an approach to show potential negative impact that appears because of potential disasters that struck. The level of landslide at Wanadri Village is based on medium threats were covering 76,81 hectares with population is 175 inhabitans threatened and high threats were covering 557,1 Hectares with population is 4.568 inhabitans threatened. The vulnerability level of landslide at Wanadri Village which is approximately from low is 3,7 Hectares and comprehensive level of medium vulnerability is 624,81 Hectares to medium. The capacity level of disaster at Wanadri Village belongs to low level because the indicator of Tangguh Village has low score or belongs to the classification of Disaster Resilient Village Primary. Comprehensive level of risk of landslide disaster at Wanadri are high risk level is 574,96 Hectares, medium risk level is 76,84 Hectares, and low risk level is 3,7Hectares.